Analisis Strategi Potensi Wisata Bahari Sebagai Kawasan Wisata Unggulan Daerah Kota Bitung - Oktaviani Ramenusa; Juliedi Manuel Palenewen (Al-Buhuts, 2025)
The purpose of this study is to identify the potential, analyze internal and external factors, and formulate development strategies for marine tourism in Bitung City to strengthen its position as a leading regional destination. A qualitative research method with descriptive analysis was employed. Data were collected from both primary and secondary sources. Primary data were obtained through field observations and interviews, while secondary data were gathered from relevant literature. The data analysis applied the SWOT framework, which systematically examines internal strengths and weaknesses as well as external opportunities and threats to formulate development strategies. The results reveal that Bitung City possesses significant strengths, including rich marine biodiversity, favorable macro-level accessibility, and government support. However, weaknesses remain in micro-level infrastructure, sea transportation, limited tourism human resources, and suboptimal promotion. Opportunities for development emerge from the growing trend of sustainable tourism, supportive government policies, and the expansion of digital promotion. At the same time, potential threats include environmental degradation, increasing competition from other destinations, and regulatory challenges. Based on the SWOT analysis, several priority strategies are recommended, namely enhancing human resource capacity, improving infrastructure, strengthening digital promotion, diversifying tourism products, and implementing conservation practices. This study highlights that Bitung’s marine tourism has strong strategic potential, particularly through the internationally recognized Lembeh Strait ecosystem, adequate macro-level infrastructure, and the commitment of local government in promoting tourism. Nonetheless, persistent challenges such as limited infrastructure, underdeveloped sea transport services, insufficient human resource capacity, and weak branding efforts need to be addressed.